Adjuvant Bidirectional Chemotherapy Using an Intraperitoneal Port - Paul H. Sugarbaker; Lana Bijelic (Gastroenterology Research and Practice)
Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) have been established as treatment options for patients with peritoneal metastases or peritoneal mesothelioma. However, this novel treatment strategy remains associated with a large percentage of local-regional treatment failures. These treatment failures are attributed to the inadequacy of HIPEC to maintain a surgical complete response. Management strategies to supplement CRS and HIPEC are indicated. A simplified approach to the intraoperative placement of an intraperitoneal port for adjuvant bidirectional chemotherapy (ABC) was devised. Four different chemotherapy treatment plans were utilized depending upon the primary site of the malignancy. Thirty-one consecutive patients with an intraoperative placement of the intraperitoneal port were available for study. The incidence of adverse events that caused an early discontinuation of the bidirectional chemotherapy occurred in 75% of the 8 patients who had an incomplete cytoreduction and in 0% of patients who had a complete cytoreduction. All of the patients who had complete cytoreduction completed at least 5 of the scheduled 6 bidirectional chemotherapy treatments. Adjuvant bidirectional chemotherapy is possible following a major cytoreductive surgical procedure using a simplified method of intraoperative intraperitoneal port placement.